2008
DOI: 10.1016/j.biopsycho.2008.04.005
|View full text |Cite
|
Sign up to set email alerts
|

Worry, generalized anxiety disorder, and emotion: Evidence from the EEG gamma band

Abstract: The present study examined EEG gamma (35-70 Hz) spectral power distributions during worry inductions in participants suffering from generalized anxiety disorder (GAD) and in control participants without a history of psychiatric illness. As hypothesized, the EEG gamma band was useful for differentiating worry from baseline and relaxation. During worry induction, GAD patients showed higher levels of gamma activity than control participants in posterior electrode sites that have been previously associated with ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
90
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 138 publications
(101 citation statements)
references
References 23 publications
10
90
1
Order By: Relevance
“…Second, it is found that the classification performance of alpha, beta, and gamma bands is better than those of delta and theta bands in both the groups. This partly reflects that higher frequency bands play a more important role in emotion activities than lower frequency bands (Oathes and Ray, 2008;Wang et al, 2013) in PD patients and HC respectively. On the contrary, previous findings of EEG-emotion correlation in theta band has been reported (Aftanas and Golocheikine, 2001;Sammler et al, 2007).…”
Section: Choosing Of Svm Kernelsmentioning
confidence: 98%
“…Second, it is found that the classification performance of alpha, beta, and gamma bands is better than those of delta and theta bands in both the groups. This partly reflects that higher frequency bands play a more important role in emotion activities than lower frequency bands (Oathes and Ray, 2008;Wang et al, 2013) in PD patients and HC respectively. On the contrary, previous findings of EEG-emotion correlation in theta band has been reported (Aftanas and Golocheikine, 2001;Sammler et al, 2007).…”
Section: Choosing Of Svm Kernelsmentioning
confidence: 98%
“…This result partly reflects that higher frequency bands play a more important role in emotion activities than lower frequency bands [63][64][65]. The current finding matches our previous study, where bispectrum emotion-specific features were mainly related to higher frequency band rather than lower frequency band in distinguishing six emotional states (happiness, sadness, fear, anger, surprise, and disgust) of PD patients and HC respectively with an averaged recognition rate of 70.10% ± 2.83% and 77.29% ± 1.73% [55].…”
Section: Resultsmentioning
confidence: 95%
“…This result shows that beta and gamma bands are the key bands in emotion recognition task. In other words, high frequency bands of EEG signals play a more important role in emotion activities than low frequency bands [22][23].…”
Section: Resultsmentioning
confidence: 99%